PSYCHOLOGYCAL WELL BEING PADA KAUM GAY DI DAERAH ISTIMEWA YOGYAKARTA - Kuni Kusuma Prahastami; Mulya Virgonita Iswindari Winta (Universitas Pahlawan, 2022)
The migration that occurred in DIY certainly gave birth to new impacts that need to be considered. One of them is the phenomenon of homosexuality, especially gay, which is usually faced by urban people. Adaptation to this gave birth to the pros and cons of non-gays against gays. This triggers the interest of researchers to dig deeper into the phenomenon of intolerance behavior carried out by non-gays against gays in DIY. Furthermore, this study seeks to find out what is the background of the intolerance towards gay people. This study uses a qualitative research method using a phenomenological approach. The respondents of this research are gay people who live in Yogyakarta. The characteristics of the respondents in this study have an age range of 19 to 33 years with differences in length of time being gay and work background. The data collection method used step-by-step and in-depth interviews and participatory observation. The results of this study indicate that each respondent experiences an intolerant attitude given by non-gays and has an impact on the psychology of each respondent. This research is expected to provide an understanding to the wider community that intolerance also has its own psychological impact on gay people. Keywords : Gay. Intolerance, Non Gay